Identifikasi Salience Stakeholders dalam Pengungkapan Sustainability Report - Yanti, Ni Putu Ayu Devi; Gayatri, Gayatri (E-Jurnal Akuntansi, 2021)
Stakeholders have their own characteristics in their approach to understanding their interests. In balancing the needs and desires of stakeholders, there are various obstacles, one of which is the level of stakeholder influence, namely stakeholder salience. This research was conducted on companies on the Indonesia Stock Exchange for the period 2017-2019 through the official website www.idx.co.id. The population of this research is 632 companies. Samples are taken using purposive sampling technique as many as 43 companies with 129 observational data. The research analysis technique is linear regression analysis and two way ANOVA test. The results showed that shareholders and environmental groups had a positive and significant effect on the disclosure area of ??the sustainability report, while consumers and the mass media which had the attributes of legitimacy and power had a negative and significant effect on the disclosure area of ??the sustainability report. Keywords: Salience; Stakeholders; Sustainability Report Disclosures.